Relationship between serum insulin-like growth factor-1, IGF binding protein-3 levels and body height before and after gonadotropin-releasing hormone agonist therapy - Han Sol Song; Won Bok Choi; Joon Sup Song; Il Tae Hwang; Seung Yang (Korean Society of Pediatric Endocrinology, 2014)
PurposeThe gonadotropin-releasing hormone agonist (GnRHa) is widely used to treat patients with precocious puberty. However, its effect on growth is often difficult to predict because of the diverse nature of its causes and presentation. This study aims to show the impact of GnRHa treatment on insulin-like growth factor-1 (IGF-I) and IGF binding protein-3 (IGFBP-3) secretion, growth, and on other parameters that may help estimate the height velocity.MethodsData from 60 girls (mean age, 8.8±0.7 years) treated with GnRHa were analyzed. Their height, bone age (BA), serum IGF-I, and IGFBP-3 concentrations were measured at the start and after a year of GnRHa treatment. To eliminate the confounding effect of chronological age (CA), the standard deviation scores (SDSs) of their height, IGF-I, and IGFBP-3 concentrations according to their CA at the start and after a year of GnRHa treatment were calculated. We looked for possible correlations between these variables and compared the subgroups based on their height velocities and midparental heights.ResultsDuring their one-year GnRHa therapy, height SDS for CA significantly decreased to 0.81±0.83 (P<0.001), but height SDS for BA increased to -0.28±0.68 (P<0.001). There was no significant change in serum IGF-I SDS, IGFBP-3 SDS, and IGF-I/IGFBP-3 ratio. The advanced BA was the factor most strongly correlated to the height velocity (R=0.265, P=0.041).ConclusionThese findings suggest that GnRHa treatment may affect the height velocity due to mechanisms other than suppression of the IGF-I and IGFBP-3 secretory axis.